STRENGTHENING ISLAMIC MORAL VALUES IN CHARACTER BUILDING FOR THE MILLENNIAL GENERATION - Syachputri, Lendy Fathmi Lia; Arif, Mahmud (Khatulistiwa, 2025)
Strengthening Islamic moral values is urgent in facing the moral challenges of the millennial generation in the digital age. The phenomena of moral decadence, individualism, and technology abuse demand educational strategies that emphasize spiritual and ethical dimensions. This study aims to analyze the role of strengthening Islamic moral values in shaping the character of the millennial generation through a literature review of the latest scientific sources. The approach used is descriptive qualitative with a literature study method, sourced from 10 national and international scientific journals and official documents from the Ministry of Education and Culture on Character Education Strengthening (PPK). The results of the study show that strengthening Islamic moral values is effective in shaping the character of the millennial generation through the internalization of the values of faith, honesty, responsibility, and social manners. Islamic morals serve as a spiritual foundation that guides the younger generation to be adaptive to global changes without losing their Islamic identity. Islamic education that integrates the aspects of faith, knowledge, and charity is a strategic path in building a generation with superior character, civility, and competitiveness in the digital age